Violence in the work of composition: recognizing, intervening, ameliorating - Gage, Scott, editor; Fleckenstein, Kristie S., editor; Utah State University Press, publisher (Colorado State University. Libraries, 2022)
Focusing on overt and covert violence and bringing attention to the many ways violence inflects and infects the teaching, administration, and scholarship of composition, Violence in the Work of Composition examines both forms of violence and the reciprocal relationships uniting them across the discipline.--Provided by publisher.
Keywords: English language -- Rhetoric -- Study and teaching (Higher) -- Social aspects; Violence in language